Strategi Pariwisata 4.0: Peran Milenial dalam Nation Branding Wonderful Indonesia 2016-2019 - Rasyidah, Resa (Global and Policy Journal of International Relations, 2019)
ABSTRACTGlobalization has had a significant impact on the development of world tourism. Technological developments in globalization have caused a shift in the industry paradigm from conventional industries to industry 4.0. From industry 4.0, the concept of tourism 4.0 emerged. Today, more and more countries are beginning to follow the concept of tourism 4.0 to develop their tourism industry to the international level. Indonesia is one of the countries implementing the 4.0 tourism concept as a strategy to develop its tourism industry through the Wonderful Indonesia nation branding. The tourism strategy 4.0 undertaken by Indonesia seeks to engage millennial to contribute to developing the Wonderful Indonesia branding nation. The aim is to increase the tourism market at both the domestic and international level. This article reviews more about Indonesia's tourism strategy 4.0 and the role of millennial in the Wonderful Indonesia nation branding 2016-2019.Keywords: Tourism 4.0 Strategy, the Role of Millennial, Nation Branding DOI : https://doi.org/10.33005/jgp.v7i02.1826